Microfluidic Roadmap for Translational Nanotheranostics. Issue 2 (26th December 2021) - Kabay, Gozde; Manz, Andreas; Dincer, Can
Abstract: Nanotheranostic materials (NTMs) shed light on the mechanisms responsible for complex diseases such as cancer because they enable making a diagnosis, monitoring the disease progression, and applying a targeted therapy simultaneously. However, several issues such as the reproducibility and mass production of NTMs hamper their application for clinical practice. To address these issues and facilitate the clinical application of NTMs, microfluidic systems have been increasingly used. This perspective provides a glimpse into the current state‐of‐art of NTM research, emphasizing the methods currently employed at each development stage of NTMs and the related open problems. This work reviews microfluidic technologies used to develop NTMs, ranging from the fabrication and testing of a single NTM up to their manufacturing on a large scale. Ultimately, a step‐by‐step vision on the future development of NTMs for clinical practice enabled by microfluidics techniques is provided. Abstract : Nanotheranostic materials (NTMs), combining on‐site diagnostics with targeted therapy, are advanced functional nanoparticles to manage complex diseases such as cancer. An insight into current microfluidic technologies used for the fabrication, characterization, preclinical, and clinical testing of NTMs, and their large‐scale manufacturing is given. Lastly, a step‐by‐step roadmap for translational NTMs development empowered by microfluidic systems is presented.